Analysis of PVD Installation Methods Due to Limited Vertical Clearance in the Lamongan North Ring Road Construction Project Section 1 STA 0+400 to STA 0+426 - Fanny Rumintha Br Barimbing; Yudhi Lastiasih; Herman Wahyudi; Sifa` Udukha (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2025)
The construction of the Lamongan North Ring Road is planned to be built on softsoil. Based on the results of the soil investigation, it is known that the subgradecondition is classified as soft to very soft soil with a depth of 18 meters. One of theproblems of this very soft soil is the settlement. Therefore, the National RoadImplementation Agency of East Java - Bali Region conducted subgrade improvementusing preloading combined with Prefabricated Vertical Drain (PVD). The configurationof the PVD installation is 18 meters deep with a triangular pattern and the distancebetween PVDs is 1 meter. To stake the PVDs 18 meters deep, a piling rig with aminimum height of 24 meters is required. In the STA 0+400 to STA 0+426 section thereis a 150 kV Lamongan - Paciran High Voltage Air Line (SUTT) cable crossing the roadwith a conductor to platform distance of 18 meters. The existence of this cable is achallenge in the PVD driving as deep as 18 meters. Therefore, this journal will analyzethe PVD piling implementation method that can be carried out in this segment. Themethod carried out in this study is to start with the collection of secondary data such asshop drawings as a reference for the implementation of work in accordance with theplanned design. Based on the design plan, an implementation method that can beapplied to limited vertical clearance conditions is obtained. Based on the results of theresearch, an 18-meter deep PVD installation method was obtained that can be applied tolimited vertical clearance conditions in the Lamongan North Ring Road constructionproject Section 1 STA 0+400 to STA 0+426. In addition, it was also found that the timerequired was 34.75 minutes to stake 1 PVD point using the pulled hole PVD method.